RELATIONSHIP OF LEARNING MOTIVATION AND ATTENTION OF PARENTS WITH MATHEMATICS LEARNING OUTCOMES OF CLASS VIII STUDENTS OF SMP NEGERI 3 WONOSARI - Herdhian Qurniawati Widyaningrum; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Student learning is influenced by several factors. Lack of student learning motivation and parental attention are some of the factors that can influence learning outcomes, so the achievement of learning is not optimal. This study aims to determine whether there is a positive and significant relationship between learning motivation and parents' attention with mathematics learning outcomes of VIII grade students of SMP Negeri 3 Wonosari odd semester 2014/2015 Academic Year. The population in this study were all students of class VIII odd semester 3 of Wonosari Middle School in the 2014/1015 Academic Year. Consisting of 6 classes with a total of 192 students. While the sample was taken VIIIF class with random sampling techniques to the class. The data collection technique was used a questionnaire method to find out about parents' motivation and attention, and documentation techniques to find out the results of learning mathematics. Data analysis using correlation analysis and linear regression analysis. The results showed there was no positive and significant relationship between (1) learning motivation with mathematics learning outcomes, with = -0.15 and = 2.04 so . Simple correlation coefficient  and linear regression equations . (2) the attention of parents with mathematics learning outcomes, with = -0.71 and = 2.04 so . Simple correlation coefficient = -0.126 and linear regression equations . (3) learning motivation and attention of parents with mathematics learning outcomes, with = 0.000365 and   so . Multiple correlation coefficient  and linear regression equations = 69.02729864+ 0,177029465X1-0.31304263X2. Relative contribution and and effective donations and  with a double determination coefficient = 0.021, this means that the learning outcomes of Grade VIII students of SMP Negeri 3 Wonosari in the odd semester of the 2014/2015 Academic Year are influenced by parents' learning motivation and attention (double determination coefficient 2.1%) while 97,927% is influenced by other factors that are not discussed in this study.